Nb-induced lattice changes to enhance corrosion resistance of Al0.5Ti3Zr0.5NbxMo0.2 high-entropy alloys - Xuelian Yu; Qingjun Chen; Xia Cui; Delai Ouyang (Nature Communications)
Abstract In this work, the effect of lattice structure on the corrosion behavior and passivation film properties of reinforced Al0.5Ti3Zr0.5NbxMo0.2 (x = 0.5,0.8,1) high-entropy alloys are investigated. A single-phase BCC Al0.5Ti3Zr0.5NbxMo0.2 (x = 0.5, 0.8, 1) high-entropy alloys, exhibiting good corrosion resistance, are synthesized using vacuum arc melting. Nb improves the corrosion resistance of high-entropy alloys in two main ways. On the one hand, the alloys show preferential corrosion at the {011} crystalline planes. Increasing Nb content reduced the {011} crystalline plane spacing, enhancing the corrosion resistance of Al0.5Ti3Zr0.5NbMo0.2. On the other hand, during the corrosion process, Nb, which has a large atomic radius and strong oxygenophilicity, interacts with each metal element, contributing to the uphill diffusion of Al/Ti and the downhill diffusion of O. The low-valent oxides form first continuously react with the inward-diffusing O to form high-valent oxides. This results in the formation of a layered passivation film with high breakdown potential and high stability. This work provides a basis for designing chemically robust alloys for extreme environments.